2006
DOI: 10.1103/physrevc.73.024310
|View full text |Cite
|
Sign up to set email alerts
|

High spin structure and intruder configurations inP31

Abstract: The nucleus 31 P has been studied in the 24 Mg( 16 O,2αp) reaction with a 70-MeV 16 O beam. A complex level scheme extended up to spins 17/2 + and 15/2 − , on positive and negative parity, respectively, has been established. Lifetimes for the new states have been investigated by the Doppler shift attenuation method. Two shell-model calculations have been performed to describe the experimental data, one by using the code ANTOINE in a valence space restricted to the sd shell, and the other by applying the Monte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Further, the predicted negative parity states in 30 Si, are in reasonable agreement with the observed level sequences. Interestingly, the calculations did not require any system dependent lowering of the single-particle energies of the f 7/2 and the p 3/2 orbitals as was found necessary in the previous studies [7,21,22]. Ref.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Further, the predicted negative parity states in 30 Si, are in reasonable agreement with the observed level sequences. Interestingly, the calculations did not require any system dependent lowering of the single-particle energies of the f 7/2 and the p 3/2 orbitals as was found necessary in the previous studies [7,21,22]. Ref.…”
Section: Introductionmentioning
confidence: 82%
“…Several studies on the sdpf nuclei have attempted to explain the observed level structures by introducing a nucleus specific reduction [21,22] in the single particle energies of the intruder levels, and have attributed the agreement of such (shell model) calculations with the deduced level structure as a signature of the reduced shell gaps. However, it may be noted that these calculations have been performed using a large model space and consequently, a truncation scheme had to be introduced owing to the computational limitations.…”
Section: Re-examining Shell Model Calculations In 30 Simentioning
confidence: 99%
“…Several different interactions were developed [4][5][6][7][8] and truncated sd-fp shell-model calculations were performed. The experimental information concerning the level scheme of many nuclei in the region was considerably extended in the last decade by using heavy-ion induced reactions and efficient γ detection systems [9][10][11][12][13][14][15][16][17][18][19][20]. The data were compared with large shell-model calculations to test the effective interactions proposed for this mass region.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [23]. An interesting feature revealed by these calculations is that the yrast negative-parity states show an alternating structure: the 7 [22] which is not sufficient to disentangle the theoretical puzzle.…”
Section: Introductionmentioning
confidence: 99%
“…Excited levels of 31 P was were previously studied in 12 C( 20 Ne,p(n)), see Ref. [22] and 24 Mg( 16 O,2αp(n)) reactions, Ref [23,24] up to high spins. In contrast, the more exotic 31 S was observed up to only 13 2 + and 13 2 − spin Ref.…”
Section: Introductionmentioning
confidence: 99%